Assessment of groundwater quality for drinking purposes using water quality index in volcanic rock areas of Axum, Northern Ethiopia - Haile Tadelle Abadi; Teka Asresie; Amdom Mihretu; Welday Gebrehiwot (Applied Water Science)
Abstract Shallow groundwater serves as the primary drinking water source in sub-Saharan Africa, including Ethiopia’s arid to semi-arid regions. However, its quality is increasingly threatened by pollution. This study evaluates the suitability of groundwater for drinking and investigates the hydrogeochemical processes that influence water quality in the volcanic rock-dominated area of Axum, Ethiopia. A total of 25 groundwater samples were collected from domestic wells and analyzed according to American Public Health Association standards. Hydrogeochemical evolution was assessed using molar ratios, multivariate statistical analysis, and inverse modeling, while the Water Quality Index (WQI) was used to determine drinking water suitability. The Inverse Distance Weighting (IDW) method mapped the spatial distribution of physicochemical parameters. The dominant water facies identified were Ca–Mg–Na–HCO3 and Mg–Ca–HCO3, with moderately mineralized Na–Ca–Mg–HCO3, Na–Mg–HCO3, and Ca–Na–HCO3 types evolving along the flow direction. Calcite, dolomite, gypsum, fluorite, and halite dissolution, along with ion exchange, controlled groundwater chemistry. Molar ratio analysis highlighted silicate and carbonate weathering, sulfate mineral dissolution, and anthropogenic influences as key factors affecting water chemistry. Several parameters, including electrical conductivity, total dissolved solids, total hardness, alkalinity, major ions, and trace metals, exceeded the permissible limits set by the World Health Organization. According to the water quality index analysis, the samples were categorized as excellent (24%), good (44%), poor (20%), very poor (8%), and unsuitable (4%) for drinking purposes. The findings highlight the need for continuous groundwater quality monitoring and the implementation of effective management strategies to ensure safe drinking water.